Tingkat Penerimaan Masyarakat terhadap Variasi Stik Berbahan Dasar Tepung Daun Katuk - Siti Suciati; Ernik Rustiana (Oksitosin : Jurnal Ilmiah Kebidanan, 2022)
Leaf Katuk sticks are sticks made from wheat flour with the addition of katuk leaf flour. Moringa leaves contain polyphenols and steroids that can increase prolactin levels which play a role in producing breast milk. The purpose of this study was to determine the level of public acceptance of variations of sticks made from katuk leaf flour. This type of research is observational with a pre experimental design. The sample used in this study was 30 panelists who were determined by accidental sampling who met the inclusion criteria and the panelists were asked to feel and assess the variation of sticks made from katuk leaves. Assessment based on organoleptic theory. The variations of the Katuk Leaf Sticks were tested for differences in the level of acceptance. Statistical analysis of the acceptance rate using the Kruskal Wallis testing technique with an alpha value of 0.05. Based on the results of organoleptic and hedonic testing from the panelists, it is known that there are differences in the level of acceptance of variations of sticks made from katuk leaves both in terms of aroma, taste, texture and color with Asymp values. Sig < 0.005. The results of the different acceptance rates for variations of the katuk leaf sticks are that there are differences in the acceptance rates for formula 1, formula 2, and formula 3 sticks . The most accepted variation of sticks made from katuk leaves is in Formula 1. Keywords: Acceptance Rate, Katuk Leaf Stick Variation, Organoleptic